Atializumab, a humanized anti-aminoacyl-tRNA synthetase-interacting multifunctional protein-1 (AIMP1) antibody significantly improves nephritis in (NZB/NZW) F1 mice. (November 2019) - Mun, Chin Hee; Kim, Jin-Ock; Ahn, Sung Soo; Yoon, Taejun; Kim, Su Jeong; Ko, Eunhee; Noh, Hee-Dong; Park, Yong-Beom; Jung, Hak-Jun; Kim, Tae Sung; Lee, Sang-Won; Park, Sang Gyu
Abstract: Aminoacyl-tRNA synthetase (ARS)-interacting multifunctional protein 1 (AIMP1) enhances the expression of proinflammatory cytokines. In our previous study, we have shown that serum AIMP1 in patients with SLE was significantly higher than that of healthy controls. To address whether neutralization of AIMP1 could ameliorate nephritis in lupus-prone mice, we generated atializumab, a humanized antibody against AIMP1 and investigated its therapeutic efficacy. ELISA showed that serum AIMP1 at 23 weeks old was significantly higher than that at 13 weeks old in lupus-prone mice. Therefore, lupus-prone mice were randomly assigned to 5 groups (vehicle, methylprednisolone and 0.5, 2, and 5 mg/kg atializumab). After treatment, disease severity was assessed using a variety of phenotypes, including proteinuria, histological damages, renal deposition of immune-complex. In addition, serum cytokines, anti-dsDNA and IgG subclasses were determined. T cell subsets were analyzed using a fluorescence-activated cell sorter. Atializumab significantly diminished proteinuria, improved glomerular and tubular damages and reduced the renal deposition of immune-complexes. Moreover, atializumab significantly decreased serum interferon (IFN)-γ, interleukin (IL)-17A, and IL-6, whereas it increased serum IL-10. Similarly, atializumab reduced the numbers of TH 1, TH 2 and TH 17 cells in a dose-dependent manner, while atializumab enhanced the number of regulatory T (Treg) cells. Furthermore, atializumab decreased not only splenic plasma cells and serum anti-dsDNA but also pathogenic IgG subclasses for nephritis. It suppressed NF-κB activation by inhibiting IκBα degradation in a dose-dependent manner in vitro . Atializumab alleviated nephritis by inhibiting autoreactive T, B, and plasma cells and decreasing NF-κB-related proinflammatory cytokines in lupus-prone mice. These results suggest that treatment targeting AIMP1 could be a novel and highly immune-modulating therapeutic strategy in lupus nephritis.